KOMPOSISI DAN STRUKTUR VEGETASI STRATA SAPLING DI KAWASAN HUTAN WISATA RIMBO TUJUH DANAU KABUPATEN KAMPAR PROVINSI RIAU - Nursal '; Yuslim Fauziah; Alzukri ' (Biogenesis, 2012)
structure of sapling strata vegetation in Hutan Wisata Rimbo Tujuh Danau Kampar regency Riau province on July 2011. Method which had been used in this research is plot method in 10 x 20 m and main plot in 20 x 20 m that’s distributed regularly. The sample was gotten from 3 locations, they are Tanjung Putus lake, Pinang Luar lake and Pinang Dalam lake which were chosen by purposive sampling. The result of this research was founded 22 species of sapling from 19 familia, they are 14 familia from 14 species of sapling in Tanjung Putus lake, 11 familia from 13 species of sapling in Pinang Luar lake and 13 familia from 16 species of sapling in Pinang Dalam lake. Dipterocarpaceae and Myrtaceae are the most of familia. The species of sapling strata vegetation that had the highest Important Value Index in Tanjung Putus lake and Pinang Dalam lake is Kuras (Dryobalanops sp.) while in Pinang Luar lake is Samoram/Cengal (Hopea mengarawan). Varians Indeks (H’) from 3 locations is about 2,298 – 2,539. Smilarity indeks on 3 research locations to be compared have some smilarity. The conclusion from the result of this research is varians of sapling strata vegetation that were founded in Hutan Wisata Rimbo Tujuh Danau can be divide to middle vegetation.Keyword : compotition, Hutan Wisata Rimbo Tujuh Danau and structure, sapling.